2012
DOI: 10.1371/journal.pone.0048350
|View full text |Cite
|
Sign up to set email alerts
|

Association between Single Nucleotide Polymorphisms (SNPs) and Toxicity of Advanced Non-Small-Cell Lung Cancer Patients Treated with Chemotherapy

Abstract: New therapeutic approaches are being developed based on the findings that several genetic abnormalities underlying non-small-cell lung cancer (NSCLC) could influence chemosensitivity. In this study, we assessed whether polymorphisms in genes of nucleotide excision repair (NER) pathway, including ERCC5, ERCC6, MMS19L, CCNH, XPC, RRM1, can affect the tolerability of platinum-based chemotherapy in NSCLC patients. We used AllGloTM probe to assess genotyping and polymorphisms in 388 stage IIIB and IV NSCLC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…SNPs have been suggested to be predictive markers of treatment response, toxicity and survival in lung cancer patients. 8,24,25 In this study, 3 investigated SNPs of p53 p. Pro72Arg, MDM2 c. 14C 309T > G and MDM2 c.¡461C > G were not associated with ORR and CBR in NSCLC patients during platinum-based chemotherapy. We found a statistically significant difference in clinical response to chemotherapy between subgroups of 57 and above 57 y ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…SNPs have been suggested to be predictive markers of treatment response, toxicity and survival in lung cancer patients. 8,24,25 In this study, 3 investigated SNPs of p53 p. Pro72Arg, MDM2 c. 14C 309T > G and MDM2 c.¡461C > G were not associated with ORR and CBR in NSCLC patients during platinum-based chemotherapy. We found a statistically significant difference in clinical response to chemotherapy between subgroups of 57 and above 57 y ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…A considerable number of studies have focused on the association between chemotherapy-related toxicity and polymorphisms in DNA repair genes. 8,24,25 Here, we focused on the association between incidence of toxicities in patients treated with platinumbased combination chemotherapy and polymorphisms of the p53 and MDM2 genes, which are involved in p53-mediated apoptosis in normal bystander cells suffering from platinum-based regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an association between XPG polymorphisms and clinical outcomes of advanced NSCLC patients, but the results are inconsistent (Zienolddiny et al, 2006;Bartolucci et al, 2009;Sun et al, 2009;Butkiewicz et al, 2011;Zhang et al, 2012). Zhang et al (2012) conducted a study in China to investigate the association between 5 SNPs in XPG and the prognosis of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2012) conducted a study in China to investigate the association between 5 SNPs in XPG and the prognosis of NSCLC patients. They reported that rs1047768 C/T and rs2296147 C/T correlated with clinical outcomes of NSCLC patients treated with platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%